(untitled) (Dermatology Reports, 2023)
Infection of the skin may be the result of an underlying disease, or lymphoma may be the primary cause. As a result, it is possible to differentiate between two types of lymphomas: primary cutaneous lymphoma and secondary cutaneous lymphoma (SCL), which is a type of systemic lymphoma that also affects the skin. The objective of the current review is to examine what is currently known about this neglected subject. Following this, SCL was examined from a clinical, histological, and survival perspective.